2019
DOI: 10.1088/1757-899x/682/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Strategic outlook in industrial design assessment based on product category

Abstract: Assessing industrial design is an intricate process of product analysis which aims to establish the quality degree of a product and considers all its implications from technical restrictions to appearance. Industrial design is related to mass produced articles obtained through industrial processes and whether products are articles of adornment or machines, both technical and aesthetic dimensions are relevant and influence the design process. All types of industrial products can be assessed using a numerical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Interpreting the analysed sections, it can be observed that a main component of product quality is associated with pre-production or production phase, such as quality planning or quality control, especially when error prevention is considered. However, approaching the study from the perspective of assessment, based on the design assessment dimensions [33], the relevant concepts associated to the relation between design and quality were structured and presented in Table 1. In order to eliminate redundancy, the recurring terms were reduced as well as the resembling concepts.…”
Section: Quality In Design Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpreting the analysed sections, it can be observed that a main component of product quality is associated with pre-production or production phase, such as quality planning or quality control, especially when error prevention is considered. However, approaching the study from the perspective of assessment, based on the design assessment dimensions [33], the relevant concepts associated to the relation between design and quality were structured and presented in Table 1. In order to eliminate redundancy, the recurring terms were reduced as well as the resembling concepts.…”
Section: Quality In Design Assessmentmentioning
confidence: 99%
“…The proposed approach to quality is user-centered as can be seen in Figure 2 and addresses the assessment dimensions in relation to conformance to the user, taking into account its typology and associated specifications. As can be observed, the functional dimension is approached differently, since functionality in design assessment has the highest ratio of importance and it does not relate directly to the products features but emphasizes the user experience [33], whereas for the other considered dimensions, the degree of conformance of the product's features can be analyzed individually for each dimension, for example the product's shape from an ergonomic point of view is addressed differently compared to its aesthetic approach.…”
Section: Quality In Design Assessmentmentioning
confidence: 99%